Non essere ancora all’altezza del tempo. Ernst Bloch su una fotografia (Materiali di Estetica. Terza serie, 2016)
What does a photographic image show? How can a photography, being an image, be connected with life, showing us unknown and mysterious aspects of our existence? Starting from a sport accident fixed in a Polaroid, Ernst Bloch thinks about the role of pictures broadcast by mass media that is in tension between hope and desperation, emancipation and enslavement, aesthetic deepening and anesthesia. Bloch in a few pages sums up his thought about our relationship with technical devices, pointing out its dual nature: on the one side the shock of the senses, on the other side the messianic salvation.